“ You are being videotaped, Smile !!!” Everyday life, Power, Surveillance and Freedom in Democratic India - Harish. G & Jasheena. P. B. (Singularities : A Transdisciplinary Biannual Research Journal, 2016)
Monitoring of people and places is in itself not new now. Vagrants, spies, trouble makers, unemployed individuals, enemies of the state etc who were seen as possible disruptive forces in any society were placed under surveillance by states across human history. In India, we can see the history and importance of surveillance well depicted in Arthashasthra by Kautilya. David Lyon defines surveillance as 'a routine and focused attention to personal details for the purposes of influence, management, care and control'. Thus, surveillance is made up of several components: the collection of data, representing this data in particular ways, interpreting those data and producing social hierarchies. Whether through CCTV, ID cards or phone-taps,surveillance is about collecting information about material bodies, single or collective in a society. Surveillance is thus the monitoring of bodies, their behavior, actions, choices, desires and even fears. Whether this involves the recording of individual bodies or group of bodies in malls, airports or traffic islands or the documentation of an individual's browsing lines, surveillance cultures focus on the body behind the action. The process of surveillance has now gone beyond bio-surveillance and has now brought under it the data basing of entire population through the apparatus of DNA, Stem cells, serums and even tissues. Thus the term surveillance has now gained a new semantic scope in this age of globalization. This paper is concentrating on how our everyday life, and freedom is now being affected by the cyclopean eye of technological surveillance hanging above our head like a sword. An attempt will also be made to look into how foucauldian power equations and concepts like panopticism are invisibly getting into the hands of democratic governments like India and implemented through the weapons of surveillance. The everyday life theories of Lefebvre also will be brought under microscopic lens in the paper investigating how the private everyday life and freedom of common men in shopping malls, airports, bus stands, railway stations, supermarkets are being watched under the disguise of safety. Attempt is also made to point fingers towards the 'invisible' ways of technological surveillance to which we are unawarely normalizing our ways of everyday life and space ie.,the part played by News papers, Visual and New Media in this attempt of neo-colonization.